Regional Tourist Organisation of the Łódź Voivodeship and its role in the processes of tourism-based local production systems’ development - Rzeńca, Piotr Krzysztof (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Whether we call them local production systems, clusters or industrial districts, all of these co-opetition arrangements can be considered stimuli in developing and implementing innovations as well as local and regional growth. The complexity of a tourist product and specific requirements connected with it make the particularly prone to the forming of clusters and cluster initiatives. In 2012 tourism industry ranked second in Poland with 27 cluster initiatives and a stable growth dynamics. Tourism is dominated by top-down initiatives, contrary to other industries, where bottom up arrangements prevail. Regional cluster initiatives may be built on regional tourist organisations. The Regional Tourist Organisation of the Lodz Voivodeship (RTO LV) was established, inter alia, to create the image of the voivodeship as an attractive tourist region, to promote tourism in the region and to improve the quality of a tourist product. Since networking of the regional economy is required, the organisation joins entities representing different industries, territorial self-government units, associations, foundations, etc. According to the Board of the RTO LV, the organisation has reached an optimum representation of various industries. The RTO LV also creates smaller clusters, which flexibly enhance its potential. Focus on networking makes the organisation closer to the network cluster idea of the OECD rather than to Porter’s co-opetition relationships. As formally, the RTO LV has not got the status of a cluster, it seems justified to use the term cluster initiative or quasi-cluster structure.